Productivity and economics of castor (Ricinus communis) – based intercropping systems under rainfed conditions - SHARMA, S K; SINGH, JAGDEV (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during rainy season of 2006 to 2009 at Dryland Research Farm of Chaudhary Charan Singh Haryana Agricultural University, Hisar with the objective to assess the productivity of castor (Ricinus communis L.) in various plant geometries and to see the feasibility of growing various intercrops in castor under rainfed conditions. Fourteen treatments consisting of castor sole at 75 cm and 90 cm, castor paired at 60:90 cm and 60:120 cm, intercropping of 1 row of greengram, moth bean, clusterbean, cowpea and pearl millet in castor paired row system of 60:90 cm and intercropping of 2 rows of greengram, moth bean, clusterbean, cowpea and pearl millet in castor paired row system of 60:120 cm were tested in randomized block design with three replications. Intercropping of 2 rows of greengram in 60:120 cm castor paired row system gave significantly higher castor equivalent yield (1.35 tonnes/ha), net returns (Rs 9 674/ha), benefit: cost ratio (1.63), monetary advantage index (2 345) and income equivalent ratio (1.71). Also, intercropping of 1 row of greengram in 60:90 cm castor paired row system was found to be more productive and remunerative than moth bean, clusterbean, cowpea and pearl millet intercropping systems. Intercropping of green gram in paired row planting system of castor either in 1 or 2 rows was found superior than other intercrops in terms of biological parameters like land equivalent ratio, area time equivalent ratio and relative crowding co-efficient.